Optimal Control in Reactive Processing for Fine Chemicals and Polymers in Stirred Jacketed Batch and Semi-Batch Reactors: A Bibliography - Stojkovic, Marija (Fine Chemical Engineering, 2023)
After World War II, scientific investigations for processing in chemical batch reactors had been started, for its “most adopted” application in the industrial sector. Taken from the industrial perspective, serious instances, unable to be endured, happen; hence, the process must be in control of, which impedes the realization of batch reactor objectives. Therewithal, with the evolution of large-scale optimization software packages, the “ease” to convert novel optimal control policies into industrial environment strategies, becomes realistic. In this work, a detailed bibliography on the optimal control functioning for reactor configuration named “stirred jacketed”, waged in batch/semi-batch processing of fine chemicals and polymers, along with methods according to this definition, is presented. To the author’s knowledge, all the existing schemes are discussed, focusing on their strong points.